Inactivation of the core cheVAWY chemotaxis genes disrupts chemotactic motility and organised biofilm formation in Campylobacter jejuni. Issue 24 (2nd December 2020) - Reuter, Mark; Ultee, Eveline; Toseafa, Yasmin; Tan, Andrew; van Vliet, Arnoud H M
ABSTRACT: Flagellar motility plays a central role in the bacterial foodborne pathogen Campylobacter jejuni, as flagellar motility is required for reaching the intestinal epithelium and subsequent colonisation or disease. Flagellar proteins also contribute strongly to biofilm formation during transmission. Chemotaxis is the process directing flagellar motility in response to attractant and repellent stimuli, but its role in biofilm formation of C. jejuni is not well understood. Here we show that inactivation of the core chemotaxis genes cheVAWY in C. jejuni strain NCTC 11168 affects both chemotactic motility and biofilm formation. Inactivation of any of the core chemotaxis genes ( cheA, cheY, cheV or cheW ) impaired chemotactic motility but did not affect flagellar assembly or growth. The ∆ cheY mutant swam in clockwise loops, while complementation restored normal motility. Inactivation of the core chemotaxis genes interfered with the ability to form a discrete biofilm at the air-media interface, and the ∆ cheY mutant displayed reduced dispersal/shedding of bacteria into the planktonic fraction. This suggests that while the chemotaxis system is not required for biofilm formation per se, it is necessary for organized biofilm formation. Hence interference with the Campylobacter chemotaxis system at any level disrupts optimal chemotactic motility and transmission modes such as biofilm formation. Abstract : Chemotaxis system is required for directed motility towards or away from specific environmental stimuli, but if inactivated, also affects the capacity to build and leave a structured biofilm.